THE IMPACT OF INTERNATIONAL FINANCIAL REPORTING STANDARD (IFRS) ADOPTION ON KEY FINANCIAL RATIOS IN NIGERIA - Lawal, Adedoyin Isola; Oseni, Ezekiel; Babajide, Abiola A.; Lawal-Adedoyin, Bukola; Bonetipin, Faith (Humanities & Social Sciences Reviews, 2020)
Purpose: This study examined the effects of the adoption of the International Financial Reporting Standard (IFRS) on the quality of financial statements of agro-allied firms in Nigeria. Methodology: Battery of unit root test techniques and co-integration tests were deployed to examine the existence of long-run impact of relevance and reliability of financial reporting as provoked by IFRS adoption. The study made use of Panel Fully Modified Least Square techniques to examine the nature of the relationship between the Pre-IFRS and Post-IFRS adoption periods. Main Findings: The study noted that IFRS adoption has a substantial effect on the reliability and relevance of financial statements. Implications: The findings of this study help in shedding light on the impact of the IFRS on financial statements' reliability and relevance of listed agro-allied firms in Nigeria. Novelty: This study offers a unique understanding of the impact of IFRS adoption on financial ratios in Nigeria.